Regulating Acidosis and Relieving Hypoxia by Platelet Membrane-Coated Nanoparticle for Enhancing Tumor Chemotherapy - Luo, Xingyu; Cao, Jian; Yu, Jianming; Dai, Dongqing; Jiang, Wei; Feng, Yahui; Hu, Yong (Frontiers in Bioengineering and Biotechnology, 2022)
Acidosis and hypoxia of tumor remains the great challenge for cancer therapy. Herein, we developed Hb-LOX-DOX-ZIF8@Platelet Membrane nanoparticles (H-L-D-Z@PM NPs) to address this problem. The lactate oxidase (LOX) could deplete intratumoral lactate adequately and amplify oxidative stress efficiently. In the meantime, hemoglobin (Hb) was intended for delivering oxygen to relieve hypoxia and boosting the catalytic activity of LOX. The coated PM bestowed active tumor-targeting ability and good biocompatibility to the nanoparticles. Moreover, the encapsulation of zeolitic imidazolate framework-8(ZIF8) offered the acid response capacity to nanoparticles. With the synergism of chemotherapy drug doxorubicin (DOX), these H-L-D-Z@PM NPs appeared excellent anti-tumor competence. Collectively, this study offered a new strategy for enhancing tumor chemotherapy by regulating acidosis and relieving hypoxia.